The Tax Court's Existence as a Judicial Institution in Indonesia - RR Dewi Anggraeni (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
Abstract:In Indonesia, the Tax Court is essential in resolving tax disputes, upholding legal certainty, and upholding justice. However, these institutions face difficult obstacles, such as the complexity of tax laws and limited resources. This research aims to determine the function and authority of the Tax Court in the context of Indonesian taxation, analyze the legal challenges and judicial processes this institution faces, and assess the efforts made to improve its existence. This research uses qualitative methods, including literature-based methodology and document analysis. Data was obtained through reviewing relevant literature, analyzing official documents related to the Tax Court, and monitoring the latest tax policies and reforms. Based on research findings, the Tax Court plays an essential role in upholding justice in the Indonesian tax system. However, difficulties posed by the complexity of tax laws and limited resources hinder the effectiveness and speed of the justice system. Therefore, to increase the existence of the Tax Court, efforts have been made to involve the public, increase transparency, and reform laws and regulations. Additional steps are needed to ensure the sustainability and effectiveness of the Tax Court as a solid and reliable Indonesian judicial institution.Keywords: Tax Court; Judicial Institution; Tax Dilemma Abstrak:Di Indonesia, Pengadilan Pajak berperan penting dalam menyelesaikan sengketa perpajakan, menegakkan kepastian hukum, dan menegakkan keadilan. Meskipun demikian, lembaga-lembaga ini menghadapi kendala yang sulit, seperti kompleksitas undang-undang perpajakan dan keterbatasan sumber daya. Tujuan dari penelitian ini adalah untuk mengetahui fungsi dan wewenang Pengadilan Pajak dalam konteks perpajakan Indonesia, menganalisis tantangan hukum dan proses peradilan yang dihadapi lembaga ini, dan menilai upaya yang dilakukan untuk meningkatkan eksistensinya. Penelitian ini menggunakan metode kualitatif, termasuk metodologi berbasis literatur dan analisis dokumen. Data diperoleh melalui kajian literatur yang relevan, analisis dokumen resmi yang berkaitan dengan Pengadilan Pajak, dan pemantauan terhadap kebijakan dan reformasi perpajakan terkini. Berdasarkan temuan penelitian, Pengadilan Pajak memainkan peran penting dalam menegakkan keadilan dalam sistem perpajakan Indonesia. Namun, kesulitan yang ditimbulkan oleh kompleksitas undang-undang perpajakan dan terbatasnya sumber daya menghambat efektivitas dan kecepatan sistem peradilan. Oleh karenanya, untuk meningkatkan keberadaan Pengadilan Pajak, upaya telah dilakukan untuk melibatkan masyarakat, meningkatkan transparansi, dan mereformasi peraturan perundang-undangan. Langkah-langkah tambahan diperlukan untuk menjamin keberlanjutan dan efektivitas Pengadilan Pajak sebagai lembaga peradilan Indonesia yang kuat dan dapat diandalkan.Kata Kunci: Pengadilan Pajak; Lembaga Peradilan; Dilema Pajak